ANALISIS TINGKAT PENGETAHUAN SISWA TERHADAP TANGGAP DARURAT KEBAKARAN PADA SMK NEGERI 7 KOTA SEMARANG - Dwina Anggraini; Suroto Suroto; Ida Wahyuni (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
SMK Negeri 7 Semarang be the school with the use of equipment and machinery of the largest electric power in Central Java. Machining Programs using the equipment and machinery that most large electric power as compared to other departments and activities are at high risk of catastrophic fires such as lab welding (welding) and the operation of the milling machine. This study aimed to analyze the student's knowledge of emergency response fire. This study used a qualitative method with indepth interview approach. Key informants in this study as many as 8 people and as many as 3 people informant triangulation. The results showed the students' knowledge is still very low in a fire emergency because there is no material on the fire emergency response delivered systematically and thoroughly to students. Activity or simulated fire evacuation drills had not been established by the school. Supporting facilities and infrastructure safety systems have not provided a complete and evenly. Safety culture applied to run static and no progress from year to year. Supervision of faculty to students when the lab is still considered optimal. Media delivery of information concerning safety, especially fire emergency has never been used, still there is a bulletin board that are not maintained and was never updated. Efforts to improve work safety system needs to be carried out and supported by all parties. Suggestion: the provision of facilities to support the safety systems work, improve the supervision of teachers, increase student awareness and safety information media optimization to be important for the creation of safety in order to prevent catastrophic fires in SMK Negeri 7 Semarang.